Gaia focused product release: spatial distribution of two diffuse interstellar bands - Schultheis, Mathias; Bailer-Jones, Coryn A. L.; Biermann, Michael; Bastian, Ulrich; Gracia-Abril, Gonzalo; Altmann, Martin; Jamal, Sara; Jordan, Stefan; Löffler, Wolfgang; Balog, Zoltan; Juaristi Campillo, Jon; Rix, Hans-Walter; et al. (Astronomy and astrophysics, 2023)
Diffuse interstellar bands (DIBs) are absorption features seen in optical and infrared spectra of stars and extragalactic objects that are probably caused by large and complex molecules in the galactic interstellar medium (ISM). Here we investigate the Galactic distribution and properties of two DIBs identified in almost six million stellar spectra collected by the Gaia Radial Velocity Spectrometer. These measurements constitute a part of the Gaia Focused Product Release to be made public between the Gaia DR3 and DR4 data releases. In order to isolate the DIB signal from the stellar features in each individual spectrum, we identified a set of 160 000 spectra at high Galactic latitudes (|b| ⩾ 65°) covering a range of stellar parameters which we consider to be the DIB-free reference sample. Matching each target spectrum to its closest reference spectra in stellar parameter space allowed us to remove the stellar spectrum empirically, without reference to stellar models, leaving a set of six million ISM spectra. Using the star’s parallax and sky coordinates, we then allocated each ISM spectrum to a voxel (VOlume piXEL) on a contiguous three-dimensional grid with an angular size of 1.8° (level 5 HEALPix) and 29 unequally sized distance bins. Identifying the two DIBs at 862.1 nm (λ862.1) and 864.8 nm (λ864.8) in the stacked spectra, we modelled their shapes and report the depth, central wavelength, width, and equivalent width (EW) for each, along with confidence bounds on these measurements. We then explored the properties and distributions of these quantities and compared them with similar measurements from other surveys. Our main results are as follows: (1) the strength and spatial distribution of the DIB λ862.1 are very consistent with what was found in Gaia DR3, but for this work we attained a higher signal-to-noise ratio in the stacked spectra to larger distances, which allowed us to trace DIBs in the outer spiral arm and beyond the Scutum–Centaurus spiral arm; (2) we produced an all-sky map below ±65° of Galactic latitude to ~4000 pc of both DIB features and their correlations; (3) we detected the signals of DIB λ862.1 inside the Local Bubble (≲200 pc); and (4) there is a reasonable correlation with the dust reddening found from stellar absorption and EWs of both DIBs with a correlation coefficient of 0.90 for λ862.1 and 0.77 for λ864.8.
Online veröffentlicht: 08. Dezember 2023
Gesehen am 08.08.2024
*Gaia Collaboration: M. Schultheis, C.A.L. Bailer-Jones, M. Biermann, U. Bastian, G. Gracia-Abril, M. Altmann, S. Jamal, S. Jordan, W. Löffler, Z. Balog, J. Juaristi Campillo, H.-W. Rix, A. Sagristà Sellés [und 391 weitere Personen]